Renal denervation treatment and device-based neuromodulation - Heuser, Richard R. (Springer, 2023)
This extensively revised edition examines renal pathophysiology and the rationale for renal denervation for the management of hypertension, as well as possible long-term benefits and risks of this therapy. Renal denervation is a minimally invasive, endovascular catheter-based procedure that makes use of radiofrequency ablation to treat resistant hypertension, with studies showing a high degree of effectiveness. The devices involved in the continued evolution of this therapy are discussed and the book incorporates analyses of the development of the technique while evaluating its cost effectiveness and future applications.Renal Denervation: Treatment and Device-Based Neuromodulation describes the technique in detail, its advances and its pitfalls. While it has been estimated that 50% of Western civilization has hypertension and approximately 20% of patients have resistant hypertension, hypertension remains the leading cause of cardiovascular morbidity and mortality thus strengthening arguments to consider a wider range of potential solutions to manage these patients